EFEKTIFITAS PELAKSANAAN PROGRAM EKSTRAKURIKULER BACA TULIS AL-QUR’AN BAGI SISWA KELAS VII MTs N SUMBERAGUNG JETIS BANTUL - Nurhafidloh Hasanah (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2013)
This research aims to measure the effectiveness of extracurricular programs in reading and writing the Koran for students of class VII MTs N Sumberagung Jetis Bantul. Ideally, MTs N Sumberagung Jetis Bantul as an Islamic-based educational institution should make students be able to read or to write the Koran properly.The results of this study are: 1. the practice of Extracurricular programs in MTsN Sumberagung Jetis Bantul is conducted in 3 methods/strategies, namely: classical, private (sorogan) and assistance. Implementation of development in accordance with the regular classes, students learn first hand the pembimbig teacher in person to person by reading the Koran or Iqra‘, memorizing short letters and prayers everyday. 2. The effectiveness of the implementation of extracurricular programs to read and write the Koran for students of class VII are as follows: a). In the context of evaluation is effective, b). In the evaluation of the input was considered quite effective, c). Upon the evaluation process is considered to be effective, d). on the evaluation of products / results considered quite effective.